Epistemologi Kritis: Telaah Pemikiran Hermeneutika Jurgen Habermas - Abd. Kholiq, Moh. Khoirul Fatih (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
Habermas hermeneutic theory is perhaps a new breakthrough to bridge the tension between objectivity and subjectivity, between ideality and reality, between theoretical and practical. And this is an achievement of Habermas in the discipline of hermeneutics. Hermeneutics, which initially focused on the area of ​​idealism, by Habermas has been pulled